Software and Hardware Decoupling of 10 kV Line Safety Protection Measurement and Control Device Based on Independent Chips - Bai, Jialin; Han, Shengguo; Niu, Jing; Qiao, Weixiang; Zhao, Wuzhi (Distributed Generation & Alternative Energy Journal, 2025)
The performance and security of 10 kV line protection and control devices are crucial given the quick expansion of the smart grid and industrial Internet of things. The traditional devices mostly use foreign chips, which have the risk of technology dependence and information security. Therefore, the research constructs a high-performance, autonomous and controllable 10 kV line protection and control device by means of independent chip selection and software and hardware decoupling method. The research utilizes the Longchip 3C6000/S chip, combined with key function modules, to build a hardware platform. The software adopts layered design to realize the separation of interface, service and application. YOLOv7 and software and hardware decoupling technology are utilized to enhance system performance and security. The experimental results indicated that the research method operated efficiently and stably on the test dataset. The initial loss value of YOLOv7 was in the range of 0.99-1.02, and approached 0 after 25–53 iterations. The training loss of YOLOv7 converged quickly, and the recognition accuracies reached 98.87% and 98.46%, respectively, with a peak hardware occupancy of 39%. The results show that the research-designed measurement and control device provides strong support for the stable operation and safe development of the power system. This method promotes the evolution of electric power secondary equipment towards autonomy, control, intelligence, and agility. It enhances the intelligence and information security capabilities of power systems.